CREATING THE EVALUATION TEMPLATE FOR THE 2017-2019 SEDGWICK COUNTY COMMUNITY HEALTH IMPROVEMENT PLAN - Powell, Matthew (My University, 2017)
A community health analysis (CHA) is a structured approach to assess the public health needs within a community in order to continue to improve the health of the people that reside there. A community health improvement plan (CHIP) is the initiative set forth from the health analysis to actively utilize community resources to improve those public health areas previously identified. In 2015, community health leaders in Sedgwick County completed the CHA and followed it by completing their CHIP in 2016. What was created was the 2017-2019 Community Health Improvement Plan for Sedgwick County. However, what was lacking was an evaluation tool that could be used to periodically assess the CHIP to ensure that the strategies being used would actually lead to the desired outcomes by the end of 2019. This is a report of my field experience for my master of public health degree in which I, with the help of Becky Tuttle and several other community health leaders, constructed the evaluation template for the 2017-2019 Sedgwick County CHIP.
Keywords: Community health; Public Health